Pusat Kreativitas Teknologi Digital Dengan Pendekatan Prinsip Desain Norman Foster Di Pekanbaru - Afyar, Aldo; Susilawaty, Mira Dharma; Faisal, Gun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The Center for Digital Technology Creativity in Pekanbaru is a facility that utilizes digital technology in creative thinking to keep abreast of digital and easy times and a place for peopleto understand and participate in developing digital technology by developing digital technology skills in various branches of technology. The existence of the Center for DigitalTechnology Creativity in Pekanbaru is very important, starting from the high interest of the community towards technology and also because digital technology has great potential in the industrial world in the digital era where everything that is done is completely digital. Theimportance of this facility is strengthened by the large number of people who start using digital technology but are not yet aware of what can be done by the technology, so that the digitaltechnology used will be felt to be useless and quite a number of cases are found due to negative use of technology. The Center for Digital Technology Creativity has the main function as a training and development center that aims to increase students' knowledge about digital technology and digital technology branches in the industrial world and information functions that will explain the technological developments in the world. This method uses the NormanFoster Design Principles Approach which applies the science of modern technology and provides ease of use. Norman Foster always designs with the inculcation of the concept of High Tech in his building, so that not only provides facilities that develop technology skills toindividuals but also illustrates a technological development into architecture that can be seen in the physical building and experience in the building. Through the Binary Digit concept thatwill express what digital technology is and the application of digital technology can be seen through the architecture of buildings.keywords : Pekanbaru, Digital Technology, Norman Foster Design Principles